Wind Effects on Rectangular and Triaxial Symmetrical Tall Building Having Equal Area and Height - Astha Verma; Rahul Kumar Meena; Hrishikesh Dubey; Ritu Raj; S. Anbukumar (Complexity)
The study aims to investigate wind effects on the equal area and the same height building model having the plan cross-sectional shape in the form of regular and irregular shape bulidings. The ratio of modification in the cross-sectional shape is kept same for regular and irregular shaped models because limited studies are available for such type of comparison. The responses of the structure to resist the wind load is increased by applying these modifications in the corner configuration such as corner cut, chamfer, and fillet in the plan shape of the structure. The numerical study is performed using ANSYS CFX and wind incidence angle varies in the range of 0° to 180° at the interval of 15°. The results of velocity and pressure distribution are presented in the form of pressure contours and wind force coefficients for all four-building models which are presented in the form of a graph. The comparison of numerical simulation results on two models are compared with the different international standards and with the experimental results. The regular shape with a corner cut and a “Y”-shaped structure with a fillet corner model performed the best among all models for resisting overall wind force. The results of pressure distribution of all four models are presented in the form of pressure contours for 0° and 90° wind angles.